2006
DOI: 10.1111/j.2042-3306.2006.tb05552.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormone response to training and competition in athletic horses

Abstract: This study shows that competition elicits a classic physiological stress response in horses and that different training programmes induce different responses. It suggests that horses involved in competition can provide a good model to study the exercise-induced stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
4
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 18 publications
5
71
4
10
Order By: Relevance
“…They found that competition induced a significant increase in blood cortisol response in both jumping and dressage horses. They conclude that competition elicits a classic physiological stress response in horses [3].…”
Section: Introductionmentioning
confidence: 99%
“…They found that competition induced a significant increase in blood cortisol response in both jumping and dressage horses. They conclude that competition elicits a classic physiological stress response in horses [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings were recently confirmed by another study in sport horses. Competing in either show jumping or dressage increased plasma cortisol and ACTH concentrations, but in experienced horses, this response was less than in non-experienced younger horses (Cayado et al 2006), indicating adaptation to the stressor over time. A rapid adaptation of horses has also been Pferdeheilkunde 24 found to the stress of loading onto a trailer (Shanahan 2003).…”
Section: Reproductive Function In Stallions Submitted To Different Stmentioning
confidence: 77%
“…The HPA axis regulates responses to various stress factors, digestion, immune response, mood and emotions, sexuality and energy expenditure/storage [11,59,104,[132][133][134] . In addition, since the HPA axis is also connected with the autonomic nervous system [135,136] , it is very important when the response of the HPA axis regulation [137] . Moreover, it has been reported that animals performing an exercise at the stress-induced physiological and environmental factors can be strongly affected [59,[137][138][139] .…”
Section: Dm and Central Nervous Systemmentioning
confidence: 99%
“…In addition, since the HPA axis is also connected with the autonomic nervous system [135,136] , it is very important when the response of the HPA axis regulation [137] . Moreover, it has been reported that animals performing an exercise at the stress-induced physiological and environmental factors can be strongly affected [59,[137][138][139] . Therefore, there would be enough possibilities to show different behavioral effects under various kinds of stress factors in exercise animal models such as metabolic DM and psychological depression/anxiety disorders.…”
Section: Dm and Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation